Keterkaitan Pengetahuan dan Kepatuhan Konsumsi Tablet Tambah Darah terhadap Kejadian Anemia pada Remaja Putri Panti Asuhan Muhammadiyah Prambanan Sleman Yogyakarta Tahun 2022: The Relationship Between Knowledge and Compliance with Blood-Supplemented Tablet Consumption with The Incidence of Anemia in Adolescent Women in The Muhammadiyah Orphanage Prambanan Sleman Yogyakarta in 2022 - Mudita Sri Hidayah; Shafira Azahra Spaer (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Based preliminary study at the Muhammadiyyah Orphanage Prambanan Sleman Yogyakarta, it was found that 4 out of 10 were anemic by measuring using a digital Hb tool, then 2 out of 10 only knew what anemia was, and out of 10 these students still did not consume iron supplement tablets. This study aims to determine the relationship between knowledge and adherence to blood supplement consumption and anemia incidence in adolescent girls at the Muhammadiyah Prambanan Sleman Orphanage, Yogyakarta. This research uses quantitative with a cross-sectional design for the data collection. The population was adolescent girls at Muhammadiyah Prambanan Orphanage Sleman Yogyakarta which amounted to 35 people and the sample was the whole population using the Total Sampling technique. This study showed a significant influence between anemia incidence in adolescent girls of Muhammadiyah orphanage Prambanan Sleman Yogyakarta obtained knowledge value P-Sig 0.025 (0.025 <0.05). It can be concluded there is a relationship between independent and dependent variables.